Environmental perception of high school students at a school in the south of the state of Amazonas (Research, Society and Development, 2020)
Environmental education is an important ally in the search for balance in the relationship between man and environment, in view of the growing environmental problems faced by humanity. For this, it is important to know the perception that individuals have of the environmental conditions of the environment where they are inserted. Based on this, the present study aimed to analyze the environmental perception presented by students of Professional and Technological Education of the integrated high school of the Federal Institute of Amazonas - Campus Lábrea. A questionnaire containing 9 multiple-choice questions was applied to students of Integrated High School of the 1st, 2nd and 3rd year of Technical Courses in Agriculture, Computer Science and Administration, totaling 93 students. The results of the research showed that the environmental perception shown by the investigated students reflects the personal experiences of each one, because their responses bring up acts and situations experienced in their city. It was possible to verify that students recognize the importance of the environment in their daily lives and see the fundamental role of the school in relation to environmental education actions. However, it is still important to develop effective environmental education practices, so that they can expand their sustainability concepts, seeking to improve environmental awareness, taking into account society's responsibility for environmental conservation and preservation in pursuit of sustainable development.